Liberalism and the American administrative state - Kravchuk, Robert S.
What are the primary obstacles to the development of a useful theory of democratic administration? Here the author orgues that American liberal thought is a major source of frustration to those who seek a theoretical base that integrates democratic and bureaucratic theory. Building on Benjamin Barber's distinction among three "dispositions" in American liberalism (i.e., minimalist, anqrchist, andrealist). The author contends that the tensions among these strands of liberalism generates a conflict between democratic and bureaucratic perspectives on governmence and precludes an effective integration of the two. He contrasts this approach with one offered by David Rosenbloom, who argues that the constitutional sep
Keywords: U.S.A.; Liberalism; Democracy; saPublic Administration